Ambient oxidation of benzene to phenol by photocatalysis on Au/Ti0.98V0.02O2: role of holes - Devaraji, Perumal; Sathu, Naveen K.; Gopinath, Chinnakonda S. (ACS Catalysis, 2014)
A potential photocatalyst with 2 atom % vanadium incorporated into the 1 lattice of disordered mesoporous titania, Ti0.98V0.02O2, (TV2) was synthesized. Au was deposited on TV2 (Au/TV2) through a photodeposition method. Structural, microscopy, and spectroscopy techniques support the incorporation of vanadium into the TiO2 lattice, and Au was deposited on the surfaces of TV2. Photocatalytic oxidation of benzene was conducted at ambient temperature under UV and/or visible light to demonstrate the catalytic activity of the Au/TV2 catalyst. The TV2 lattice exhibits a quantum jump in benzene to phenol oxidation compared to that of TiO2, highlighting the importance of V for oxidation. Introduction of Au onto TV2 further increases the benzene to phenol oxidation and phenol yield by a factor of 2 under UV light compared to those of bare TV2. No significant phenol production was observed in visible light with or without gold, indicating the role of gold is indirect toward charge separation and electron storage. Nano gold clusters on TV2 selectively store photoexcited electrons and in turn maximize holes utilization on TiO2. The high photocatalytic activity of Au/TV2 is mainly attributed to the presence of Schottky junctions, disordered mesoporosity, and short diffusion lengths for charge carriers.
Keywords: nano gold; phenol; Photocatalysis; Schottky junction; titania; Vanadium

Green leaf to inorganic leaf: a case study of ZnO - Sathu, Naveen K.; Devaraji, Perumal; Gopinath, Chinnakonda S. (Journal of Nanoscienceand Nanotechnology, 2016)
Can we use green leaves, available freely in our gardens, as a template for making inorganic leaf, while retaining the nanospace available within the leaf architecture. The answer is 'yes', and it is demonstrated with inorganic leaf made up of ZnO, by intercalating Zn2+ ions into the porous channels of the champa (Plumeria, Magnolia champaca) tree leaves. TEM studies reveal a variety of macro-micro-nanospace available in the inorganic leaf ZnO (IL-ZnO), and suggest the possibility of exploiting the same to produce natural nano-architecture for various applications. A speciality of the present work is the maximum suppression of defects in photoluminescence of IL-ZnO leaf, compared to the commercial ZnO, which is exploited for light harvesting through chemical conversion. Benzene to phenol conversion was studied in UV light and IL-ZnO show significant conversion and yield demonstrating C-H activation at ambient temperature.

Pt - g-C3N4 - (Au/TiO2): electronically integrated nanocomposite for solar hydrogen generation - Devaraji, Perumal; Gopinath, Chinnakonda S. (International Journal of Hydrogen Energy, 2018)
A potential nanocomposite photocatalyst was designed by integrating Pt nanoclusters (co catalyst and electron sink) with graphitic carbon nitride (g-C3N4 (gcn)) (charge diffusion) and 0.5 wt % Au containing Au-TiO2 (AuT) (plasmonic on semiconductor) for solar water splitting (SWS). Variety of Pt-gcn-AuTiO2 compositions has been evaluated for SWS under one sun conditions. Complexity of the photocatalyst was increased systematically from Au-TiO2, gcn-TiO2 to Pt-gcn-Au-TiO2 to explore the influence of different combinations. Electronic integration of charge separation/diffusion component (gcn) with light absorbing sensitizer components (Au and gcn), and co-catalyst (Pt) seems to be the critical factor to improve hydrogen yield (HY) or overall efficiency. Although addition of gcn increase the HY of composites, there is no SWS activity observed on bare TiO2 or gcn. Au or Pt on gcn enhances the charge separation effectively and interface between Au and/or Pt with gcn works as the Schottky barrier. A monodispersion of Au over TiO2 and Pt nanoclusters over gcn/AuTiO2 composite lead to the maximum solar hydrogen yield (1.52 mmol/h g) with an apparent quantum yield (AQY) of 7.5%. Photoelectron and photoluminescence spectral studies confirm the electron transfer from Au to gcn, and Au and/or gcn to titania. A thorough physico-chemical investigation of various composites underscores the electronic integration aspects of the nanocomposite towards storage of electrons in the Pt co-catalyst and hence an effective charge separation and an increase in AQY. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Electronic integration; Photocatalysis; Schottky barrier; Solar hydrogen; water splitting